Numerical and experimental analysis of a shear connection made using a top-hat profile = Analiza numeryczna i doświadczalna połączenia ścinanego wykonanego za pomocą łącznika kapeluszowego - Helbrych, Paweł; Major, Maciej; Nawrot, Jacek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper proposed a numerical model of a shear connection between a reinforced concrete slab and a steel shape. The connection was made using a top-hat profile. A method for conducting experimental research on shear connections in the composite structures was presented. Geometric dimensions and material parameters of the analysed model of connection, on which the experimental research was conducted, were noted. The results of the conducted experimental research were compared to the results of the numerical analysis performed using ANSYS software. displecement curves were analysed for both cases and any correlation between experimental and numerical results was noted.
Keywords: composite structures; top-hat profile; ANSYS; numerical analysis; experimental analysis; konstrukcje zespolone; łącznik; analiza numeryczna; analiza doświadczalna